Activity of eribulin mesylate in patients with soft-tissue sarcoma: a phase 2 study in four independent histological subtypes - Schöffski, Patrick; Ray-Coquard, Isabelle Laure; Cioffi, Angela; Bui, Nguyen Bin; Bauer, Sebastian; Hartmann, Joerg Thomas; Krarup-Hansen, Anders; Grünwald, Viktor; Sciot, Raf; Dumez, Herlinde; Blay, Jean-Yves; Le Cesne, Axel; et al. (The lancet. Oncology, 2011)
Background - Eribulin inhibits microtubule dynamics via a mechanism distinct from that of other tubulin-targeting drugs, inducing cell-cycle arrest and tumour regression in preclinical models. We assessed the activity and safety of eribulin in four strata of patients with different types of soft-tissue sarcoma. - Methods - In this non-randomised multicentre phase 2 study, patients were included if they had progressive or high-grade soft-tissue sarcoma and had received no more than one previous combination chemotherapy or up to two single drugs for advanced disease. They were stratified by the type of soft-tissue sarcoma they had. Eribulin was given intravenously at a concentration of 1·4 mg/m2 over 2-5 min at days 1 and 8 every 3 weeks to primarily assess progression-free survival at 12 weeks (RECIST 1.0), which we evaluated in all patients who started treatment. Safety analyses were done in all patients who started treatment. This trial is registered at ClinicalTrials.gov, number NCT00413192. - Findings - Of 128 patients included, 37 had adipocytic sarcoma, 40 had leiomyosarcoma, 19 had synovial sarcoma, and 32 had other sarcomas. 12 (31·6%) of 38 patients with leiomyosarcoma evaluable for the primary endpoint, 15 (46·9%) of 32 patients with adipocytic sarcoma, four (21·1%) of 19 with synovial sarcoma, and five (19·2%) of 26 in other sarcomas were progression-free at 12 weeks. The most common grade 3-4 adverse events were neutropenia (66 [52%] of 127 patients evaluable for safety), leucopenia (44 [35%]), anaemia (nine [7%]), fatigue (nine [7%]), febrile neutropenia (eight [6%]), abnormal alanine aminotransferase concentrations (six [5%]), mucositis (four [3%]), and sensory neuropathy (four [3%]). - Interpretation - Eribulin deserves further study in this setting, based on progression-free survival at 12 weeks in leiomyosarcoma and adipocytic sarcoma. - Funding - Eisai Limited, Hatfield, UK.
Gesehen am 25.10.2022